Joint effect of physical factors of different nature on the human - Aleksandr I. Sidorov (Perm Journal of Petroleum and Mining Engineering, 2018)
Modern working conditions of miners in the mining industry are characterized by intensive noise and vibration, high dustiness, unfavorable microclimate, the levels of which often exceed hygienic standards. Unfortunately, the current regulatory framework does not take into account the fact that in real life most of the production personnel are exposed not to one but several factors of the working environment at the same time. Thus, the sanitary standarts established for factors that act singularly and guarant the preservation of health precisely for these conditions may be untenable. Ensuring sustainable safety when working in electrical installations should be achieved by complying with electrical safety requirements. But permissible levels of contact currents and voltages currently recommended by the International Electrotechnical Commission do not take into account the joint effect of electric current and other physical factors, and noise in particular. The effect of sound pressure level and its frequency on the resistance of the human body is proved earlier in V.V. Katsay's thesis. The study of the effect of noise on magnitude of threshold perceptible current is resumed in laboratory conditions at the Department of Life Safety of the South Ural State University. To obtain reliable results a test complex was designed and built. The complex includes a muffled chamber, sources of simulated voltages and noise, a block of recording instruments. Primary electrical safety criteria are investigated for an increased frequency (5000 Hz) under the influence of noise load. Voltages and currents that cause feelings are measured before the impact of noise and under the influence of noise with a sound pressure level of 97 dB. The dependence built calls into question the result obtained from results of previous studies on the need to reduce settings at which tools of safety shutdown trigger.